Pharmacological effects on oxidative stress no-dependent mechanisms in the brain under chronic alcohol intoxication: angiolin antioxidant effects - Pavlyuk, I. V.; Belenichev, I. F.; Kucherenko, L. I.; Бєленічев, Ігор Федорович; Кучеренко, Людмила Іванівна (Global Science Center LP, 2016)
The aim of this work was to study antioxidant effect of the new original neuro- and cardioprotector with endothelium protective properties – "Angiolin" ((S) -2,6- diaminohexanoic acid 3-methyl-1,2,4- thiazolyl -5-thio-acetate) in modeling of chronic alcohol intoxication on the effect on the basic indicators of the NO system and oxidative stress. Under forming chronic alcohol intoxication in rats within30 days in the control group we regis-tered the disorders in the nitrergic brain system (increase in the NOS activity, hyper-NO, L-arginine deficiency), that led to the activation of oxidative stress, as evidenced by the increase in oxidative protein modifications prod-ucts and nitrotyrosine. 14-day therapy with Angiolin (100 mg/kg, intragastrically) after the 30-day alcoholization had a normalizing effect on the studied indicators of the NO system – the level of stable NO metabolites was decreased, the NOS activity was decreased in the setting of increasing concentrations of L-arginine. These positive changes under the influence of Angiolin in nitrergic brain system of animals with chronic alcohol intoxication proceeded in the setting of significant decrease of nitrotyrosine, adelhydfenihydrazones and carboxylfenihydra-zones, indicating significant inhibition of oxidative stress. Angiolin authentically exceeds the reference medication Mildronate (250 mg/kg, intragastrically) by virtue of the antioxidant action for all studied indicators. The results are experimental justification for the inclusion of Angiolin in the traditional treatment of alcoholism.
Keywords: chronic alcohol intoxication; the NO system; oxidative stress; Angiolin; Mildronate